Analisis Pengaruh Komposısı Kepemılıkan Terhadap Manajemen Laba - Shiwa, Yumy; Karina, Ria (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2023)
The basis for the findings of this study is of course based on an objective of analyzing the factors that influence family ownership, institutional ownership, and blockholder ownership on earnings management. These factors can affect earnings management. A purposive sampling approach was used to select a sample of 228 public finance companies from 2017 to 2021 that are listed on the IDX. Of course, this study uses the panel data regression method which combines cross-sectional and time series data. Among the techniques used are outlier tests, descriptive statistics, F and t tests, and R2 tests. This study is based on a random effects model (REM). The results of the research base interpret that family ownership and institutional ownership are certainly able to have a significant positive influence on earnings management, but blockholder ownership is not necessarily able to have a significant influence on earnings management.